PENGEMBANGAN PROGRAM PELATIHAN UNTUK MENINGKATKAN KOMPETENSI GURU DALAM MEMFASILITASI KETERAMPILAN BERPIKIR KRITIS ANAK USIA DINI - Witarsa, Ramdhan (Tunas Siliwangi, 2015)
National Education Standards Agency (BSNP 2010) the Paradigm of National Education 21st Century stated that the strategy of educational attainment in the future one is to apply the methods of teaching and learning creative adhered to the principle that every individual isunique and has the talent of each, then teaching and learning methods should also pay attention to the diversity of "learning style" of each individual. The method used is the research and development of education (Education Research and Development) Borg & Gal (1991) to the stages develop products through the systematic procedures and conducted field tests, evaluation, and revision to obtain a certain quality criteria or reach certain standards. From the results of questionnaire analysis of critical thinking skills of teachers on aspects of science membelajarkan obtained a description that early childhood teachers as much as nine teachers from 12 teachers who fill in the questionnaire (75%) say that the subject matter of early childhood science is nothing difficult and nothing is easy. A total of two teachers (16.67%) said that the subject matter of early childhood science is not difficult, and as a teacher (8.33%) did not know. The efforts undertaken teachers in the face of adversity to the materials sciencedifficult, as follows: study themselves subject matter subject matter of science ECD (seven teachers), asking colleagues (eight teachers), looking for teaching materials more understand and be understood (one teacher), science reference books (three teachers), searching formaterial on the internet (seven teachers). On research and development has produced: (1) product PPMSBKBKKMRTM with its characteristics, and after implementation PPMSBKBKKMRTM may actually enhance critical thinking skills of teachers, (2) the abilityof teachers in preparing RPH-based critical thinking skills, and (3) the ability of teachers in implementing the learning science-based critical thinking skills. educational institutions or education activist groups that will carry out the in-service program by adopting PPMSBKBKMRTM need to prepare a Human Resources (HR) be it human, infrastructure and ingredients, the program implemented consistently and to a minimum in order to reduce the constraints that exist. Keywords: Training Program, Teachers Competence, Critical Thinking Skills.